A coordinated control law for inlet/outlet independent regulation of electro-hydraulic speed control system under sustained negative load. (May 2020) - Liu, Wei; Li, Yunhua; Li, Dong
Negative load operation is an inevitable operating condition for a completed task cycle of electro-hydraulic speed control system. In this working condition, to coordinate both tracking control and speed smooth regulation is necessary for avoiding stall. In this paper, a nonlinear coordinated control law aiming at independent regulation of inlet/outlet oil of valve-controlled electro-hydraulic speed system under sustained negative load is proposed. The overall control system can be divided into position tracking control subsystem and speed smooth control subsystem according to the function of the system operation. First, the coordinated control strategy is designed according to the requirements of speed tracking and speed smoothing. Then, for the coupling control problem existed in the system, a novel control law based on objective acceleration planning and expected back-pressure planning is presented. Furthermore, specified on the problem of uncertain random disturbance in practical applications, the extended state observer is designed, extending the summation of uncertain stochastic disturbance under sustained negative load into a new state variable. Finally, addressing the coordinated control strategy with expected back-pressure planning, we designed nonlinear decoupling control laws by using backstepping sliding mode robust control and backstepping sliding mode control based on extended state observer, respectively. The results of simulation and experiment show that the proposed nonlinear coordinated control strategy can provide the excellent coordination and robust performance for tracking control and speed smooth regulation.